2006
DOI: 10.1007/s10800-006-9216-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrodynamics on Faradaic current efficiency in a fluorine electrolyser

Abstract: International audienceA fluid dynamics simulation was used to study the effect of the internal movement of hydrogen bubbles on current efficiency in a pilot scale fluorine electrolyser. Two dimensional modelling of the gas–liquid free convection was carried out using the Estet-Astrid (EA) finite volume code. The effect of hydrodynamics is well highlighted and calculations show that a significant fraction of the hydrogen bubbles can migrate, under certain conditions, into the fluorine compartment. This fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 7 publications
(10 reference statements)
2
12
0
Order By: Relevance
“…In industrial reactors, large gas release may however strongly influence the electrolyser performance due to hydrodynamic modifications [8] and decreases electrolyte conductivity. These phenomena are examined here, where the process sensitivity to either operating conditions or unknown parameters, such as H 2 bubble size and departure angle, is investigated.…”
Section: Overview Of Electrolyser Modelling Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…In industrial reactors, large gas release may however strongly influence the electrolyser performance due to hydrodynamic modifications [8] and decreases electrolyte conductivity. These phenomena are examined here, where the process sensitivity to either operating conditions or unknown parameters, such as H 2 bubble size and departure angle, is investigated.…”
Section: Overview Of Electrolyser Modelling Approachesmentioning
confidence: 99%
“…A k- turbulence model is also used in [3] and [8]. A less CPU-consuming model based on mixture-lengths is used in [4].…”
Section: Governing Equationsmentioning
confidence: 99%
“…H. Roustan [1] has shown that to some extent the large gliding fluorine bubbles drag the electrolyte up along the anode. A numerical model was gradually developed in France to account for all the strongly linked phenomena involved in fluorine electrolysis [2][3][4][5][6]. The final numerical model combined two commercial codes, Flux-Expert (FE) and Estet-Astrid (EA), both distributed by Astek [7,8].…”
mentioning
confidence: 99%
“…The Estet-Astrid code took into account the forces acting on individual bubbles, namely buoyancy, drag force, lift force and added mass. Thanks to EA, Espinasse et al estimated the fraction of the hydrogen plume that recombines with fluorine and thereby decreases Faraday current efficiency in an industrial fluorine electrolyser [6]. Since the plume of hydrogen bubbles is so important in a fluorine electrolyser, experimental work was carried out to validate the accuracy of plume prediction by EA.…”
mentioning
confidence: 99%
See 1 more Smart Citation